THE ASSOCIATION OF THE LEVEL OF DISCOMFORT AND WORKSTATION DESIGN AMONG DESK JOB WORERS IN THE TELECOMMUNICATION INDUSTRY - Syafiq D.R, Ilyas; Hajar N.Z, Siti; Andy, Onery (LPPM Universitas Duta Bangsa Surakarta, 2023)
Musculoskeletal Disorders (MSDs) are a prevalent condition that affects computer users with poor posture. Office workers are affected because they utilize computers to enter data, write letters, send emails, organize meetings, and communicate with coworkers and clients. Workers in the services sector use computers, phones, work documents, and stationery to communicate with consumers. To assess the level of discomfort for WRMSDs among desk job workers and the association with workstation design. 108 people took the online CMDQ, and 27 were chosen to assess the ROSA based on their scores. Upper back (13.9%), lower back (12.0%), and hip/buttocks (10.2%) reported the most discomfort. 26 (96.3%) participants were high-risk for ROSA and 3.7% were low risk. The result of the association showed that there was no association between the level of discomfort and workstation design. Each body part showed to have a p-value>0.05 associated with workstation design. Those with desk jobs in the telecommunication industry reported feeling the most discomfort in their upper back, lower back, and hip/buttock. The result of grand ROSA showed participants having a high risk of ROSA which required a further assessment. However, there was no significant association between the level of discomfort and workstation design. The finding of ROSA does not relate directly to the bad equipment in the workplace reported by the workers but rather to the improvement of worker’s posture, optimizing its use and findings can support the result of this study.